The influenza NS1 protein: what do we know in equine influenza virus pathogenesis? - Barba, Marta; Daly, Janet M. (MDPI, 2016)
Equine influenza virus remains a serious health and potential economic problem throughout most parts of the world, despite intensive vaccination programs in some horse populations. The influenza non-structural protein 1 (NS1) has multiple functions involved in the regulation of several cellular and viral processes during influenza infection. We review the strategies that NS1 uses to facilitate virus replication and inhibit antiviral responses in the host, including sequestering of double-stranded RNA, direct modulation of protein kinase R activity and inhibition of transcription and translation of host antiviral response genes such as type I interferon. Details are provided regarding what it is known about NS1 in equine influenza, especially concerning C-terminal truncation. Further research is needed to determine the role of NS1 in equine influenza infection, which will help to understand the pathophysiology of complicated cases related to cytokine imbalance and secondary bacterial infection, and to investigate new therapeutic and vaccination strategies.